The efficacy and safety of addition of pegylated interferon to long-term nucleos(t)ide analogue therapy on functional cure of chronic hepatitis B patient: a systematic review and meta-analysis - Zhang, Xu; Yang, Xianzhao; Tan, Lingjie; Tian, Yujia; Zhao, Zhiren; Ru, Shuying (Frontiers in Pharmacology, 2024)
Objective: This meta-analysis aims to assess the efficacy and safety of adding pegylated interferon (Peg-IFN) to long-term nucleos(t)ide analogs (NAs) treatment for achieving functional cure in patients with chronic hepatitis B (CHB).Methods: This meta-analysis was registered in PROSPERO (CRD42024519116). We searched PubMed, Embase, Cochrane Library and Web of Science for randomized controlled trials that compared adding Peg-IFN to long-term NAs with NAs alone for the treatment of CHB. Relative risks (RR) and 95% confidence interval (CI) were pooled using a random-effects model.Seven trials with 692 participants were included. Compared to NAs monotherapy, sequential combination therapy significantly increased the HBsAg seroclearance rate (RR 4.37, 95%CI: 1.92-9.55; I 2 =0%) and HBsAg seroconversion rate (RR 3.98, 95%CI: 1.50-10.54; I 2 =0%), and the results reached statistical significance. Compared to NAs monotherapy, sequential combination therapy showed a significant increase in HBeAg seroclearance rate (RR 2.04; 95%CI: 0.47-8.82; I 2 =73%) and HBeAg seroconversion rate (RR 2.10; 95%CI: 0.41-10.71; I 2 =67%), but did not reach statistical significance. Sequential combination therapy was more likely to experience adverse events. Although most reactions are mild and reversible, vigilant monitoring for treatment-related adverse events is essential, with prompt intervention when needed.2 Conclusion: For CHB patients on long-term NAs treatment, sequential combination therapy boosts HBsAg seroclearance and HBsAg seroconversion rates compared to monotherapy. However, it may increase adverse events. Additional studies are needed to thoroughly evaluate its clinical effectiveness, given the current limited research available.